Checklist: Gender Considerations for Climate Services and Safety Nets - Gumucio, Tatiana; Schwager, Saroja (2019)
“Climate services” refers to the “production, translation, transfer, and use of climate knowledge and information in climate-informed decision making and climate-smart policy and planning” (Climate Services Partnership). Climate services can be a critical means of resiliency-building for smallholder farmers. However, due to gender-related factors, women and men can face differing challenges and opportunities to access climate-related information as well as using it to improve management and benefitting from those improved management decisions. To ensure equal distribution of benefits and promote gender equality, it is critical that food security and climate-resiliency initiatives take into account gender considerations from the earliest planning stages. CCAFS has developed a checklist to guide the consideration of gender issues in climate services projects.